Factores socioeconómicos y su relación con el consumo de telefonía móvil en la región Loreto durante el período 2011–2019 - Valdivia Bardales, Amel Ferdinam (2023)
Today's communication services are important as a single access point for fast and efficient communication around the world. Likewise, these services increase the dynamism of economic and productive activities by facilitating access to important information, in addition, facilitating access to various basic services, especially services such as health and education and thus encourage economic growth and the consequent increase in social welfare at the micro and macroeconomic level in the region and also in the country. Taking this into account, the objective of this study is to determine the relationship between socioeconomic factors and access to mobile telephony in the Loreto region from 2011 to 2019. For this, we use a non-experimental methodology, correlational level and type or style. quantitatively, the study had as study population all the citizens of the Loreto region and we found that socioeconomic factors such as income, spending, working hours, age and level of education, have a direct relationship with the consumption or access to mobile telephony in the Loreto region, and similarly, belonging to the informal sector has an inverse relationship with access to mobile telephony in the department of Loreto.